2019
DOI: 10.1080/23802359.2019.1567292
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome sequence of Elatostema dissectum (Urticaceae)

Abstract: The complete chloroplast genome of Elatostema dissectum Wedd. was reported in this study. The cp genome was 150,302 bp in length including two inverted repeats (IRs) of 24,565 bp, which were separated by LSC and SSC of 83,998 bp and 17,174 bp, respectively. The GC content was 36.2%. The genome encoded 112 functional genes, including 79 protein-coding genes, 29 tRNA genes, and 4 rRNA genes. This plastid genome is the first report for the tribe Elatostemateae in Urticaceae, which will be useful data for developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
6
5
0
2
Order By: Relevance
“…Our assembly results showed that the lengths of the 4 plastid genomes ranged from 150, 398 bp to 152,327 bp and that they have a typical tetrad structure. In terms of structure, these results are similar to those of most Urticaceae plants [35,36]. In this study, the longest and shortest plastid genomes in Urticaceae were 159,085 bp (Gonostegia hirta) and 146,842 bp (Hesperocnide tenella), respectively.…”
Section: Conserved Genome Structure and Gene Contentsupporting
confidence: 86%
“…Our assembly results showed that the lengths of the 4 plastid genomes ranged from 150, 398 bp to 152,327 bp and that they have a typical tetrad structure. In terms of structure, these results are similar to those of most Urticaceae plants [35,36]. In this study, the longest and shortest plastid genomes in Urticaceae were 159,085 bp (Gonostegia hirta) and 146,842 bp (Hesperocnide tenella), respectively.…”
Section: Conserved Genome Structure and Gene Contentsupporting
confidence: 86%
“…Our assembly results showed that the length of 4 cp genomes ranged from 150,398 bp to 152,327 bp. This result is similar to most Urticaceae plants [43,44]. In our study, the longest and shortest cp genome sequences in Urticaceae are 159,085 bp (Gonostegia Hirta) and 146,842 bp (Hesperocnide Tenella), respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Plastome provides sufficient information to resolve the phylogenetic relationships at generic and infrageneric level. Despite several plastid genomes of species in Urticaceae have been reported (Wu et al 2017;Wu et al 2018;Fu et al 2019;Wang et al 2020), none of them belong to Procris.…”
mentioning
confidence: 99%